Das kulturelle Gedächtnis - Assmann, Jan (Beck, 1992)
Jan Assmann:
Literaturverz. S. [305] - 325
Keywords: Civilization; Ancient; Memory; Collective memory; Group identity; Interpersonal communication; Written communication; Politics and culture; Altertum; Schrift; Geschichtsbewusstsein; Kulturelle Identität; Politische Kultur; Mittelmeerraum